(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the nutritional status of patients with chronic renal failure undergoing dialysis at Duc Giang General Hospital in 2022-2023. Methods: The cross-sectional study was conducted on 174 patients with chronic renal failure patients undergoing dialysis at Duc Giang General Hospital from August 2022 to February 2023. Results: The nutritional status according to the weight loss index accounted for nearly 6%, of which 5.2% was moderate weight loss, while 0.6% was severe weight loss. Nutritional status according to BMI was 63.8% with normal BMI, BMI<18.5 group accounted for 23.6%, overweight and obesity rate was 12.7%. Based on arm circumference, nutritional status showed that malnutrition accounted for 32.2% of patients. Nutritional status according to biochemical indicators: Low blood cholesterol index accounted for 2.9% of patients, low albumin index accounted for 48.9% and albumin index accounted for 50% of patients. Overall assessment: 44.8% of patients with energy malnutrition (≥3 criteria). Conclusion: Patients with end-stage chronic renal failure need regular attention to the examination of nutritional indicators to prevent and treat malnutrition.